2020
DOI: 10.1093/sleep/zsaa128
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal ideation is associated with nighttime wakefulness in a community sample

Abstract: ABSTRACT Study Objectives Nocturnal wakefulness is a risk factor for suicide and suicidal ideation in clinical populations. However, these results have not been demonstrated in general community samples or compared to sleep duration or sleep quality. The present study explored how the timing of wakefulness was associated with suicidal ideation for weekdays and weekends. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 47 publications
1
16
0
1
Order By: Relevance
“…These patterns—and their approximate timing—bear strong similarities to those documented during in-lab circadian and sleep deprivation experiments (e.g., Emens et al, 2020). The overnight peak in negative affect is of clinical interest because it may be one of several factors contributing to the higher risk of suicide during the circadian night (Tubbs et al, 2020b; Tubbs et al, 2021a; Tubbs et al, 2021b). It is possible that people who are awake in the middle of the night experience the full brunt of the peak in negative affect at a time when most are shielded from it because they are sleeping (Emens et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…These patterns—and their approximate timing—bear strong similarities to those documented during in-lab circadian and sleep deprivation experiments (e.g., Emens et al, 2020). The overnight peak in negative affect is of clinical interest because it may be one of several factors contributing to the higher risk of suicide during the circadian night (Tubbs et al, 2020b; Tubbs et al, 2021a; Tubbs et al, 2021b). It is possible that people who are awake in the middle of the night experience the full brunt of the peak in negative affect at a time when most are shielded from it because they are sleeping (Emens et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…If the answer was "Yes, " the student was considered as experiencing suicidal ideation in the past year. Similar methodology has been followed in previous studies on suicidal ideation (13,21,34,35).…”
Section: Suicidal Ideationmentioning
confidence: 99%
“…Nocturnal wakefulness may also increase risk for suicidal thinking. Objectively-measured wakefulness at 4 AM predicted next-day suicidal ideation in individuals with treatment-resistant depression ( Ballard et al, 2016 ), and self-reported wakefulness between 11 PM and 5 AM was associated with greater likelihood of suicidal ideation in both community ( Tubbs et al, 2020a ) and national samples ( Tubbs et al, 2021 ). A similar pattern emerges when examining data from the Internet forum Reddit: posts on a subforum called “SuicideWatch” peaked between 2 AM and 5 AM, whereas posts on a non-suicide related subforum called “AskReddit” peaked between 8 PM and 11 PM ( Dutta et al, 2021 ).…”
Section: Nocturnal Changes In Dysregulated Behaviormentioning
confidence: 99%